Penerapan Sistem Informasi Website Desa Dolopo Dalam Pelayanan Publik Di Desa Dolopo Kecamatan Dolopo Kabupaten Madiun - Purwandari, Nur Alifia; Prasetyawan, Agus (Universitas Negeri Surabaya, 2024)
The implementation of Dolopo Village's website information system is still fairly ineffective. To increase the value of information systems in public services, Dolopo Village decided to create a website called